Effect of Financial Literacy and Lifestyle of Finance Student Behavior - Ade Gunawan; Chairani Chairani (International Journal of Business Economics (IJBE), 2019)
This study aims to examine the relationship between financial literacy and financial behavior of the lifestyle of the student and determine differences in financial literacy, lifestyle and behavior of student finance and business economics faculty. This research is quantitative data collection techniques using questionnaires. Sample used were 100 students consisting of students of the faculty of economics and business Muhammadiyah University of North Sumatra, this study uses judgment sampling. Data were analyzed using classical assumption test, multiple linear regression, t test, F test, and the coefficient of determination. Research shows that financial literacy has no effect on the financial behavior.